VINYL : Owners' Workshop Manual : How to get the best from your vinyl records and kit (Sparkford : Haynes Publishing, 2017)
188 pages of vinyl tech and technique, with hints and tips from the world's top professionals.
Includes index.
Keywords: Phonograph -- Handbooks, manuals, etc; Sound recordings; Music; Handbooks and manuals